Contractile reserve as a predictor of prognosis in patients with non-ischaemic systolic heart failure and dilated cardiomyopathy: a systematic review and meta-analysis - Peter H Waddingham; Sanjeev Bhattacharyya; Jet Van Zalen; Guy Lloyd (Echo Research and Practice, 2017)
Objective: Patients with non-ischaemic systolic heart failure (HF) and idiopathic dilated cardiomyopathy (DCM) are a heterogenous group with varied morbidity and mortality. Prognostication in this group is challenging. We performed a systematic review and meta-analysis to examine the significance of the presence of contractile reserve as assessed via stress imaging on mortality and hospitalisation. Methods: A search for studies that non-invasively assessed contractile reserve in patients with DCM or non-ischaemic HF with reduced ejection fraction, stress imaging with follow-up data comparing outcomes. A range of imaging modalities and stressors were included. We examined primary endpoints of mortality and secondary endpoints of combined cardiovascular events including HF progression or hospitalisation. Our analysis compared endpoints in patients with contractile reserve and those without it. Results: Nine prospective cohort studies were identified describing a total of 787 patients. These studies are methodologically but not statistically heterogenous (I2 = 31%). Using a random effect model, the presence of contractile reserve was associated with a significantly lower risk of mortality and cardiovascular events odds ratios of 0.20 (CI 0.11, 0.39) (P < 0.00001) and 0.13 (CI 0.04, 0.40) (P = 0.0004), respectively. Conclusion: Regardless of stressor and imaging modality and despite the significant methodological heterogeneity within the current data (imaging techniques and parameters), patients with non-ischaemic cardiomyopathy and reduced EF who demonstrate contractile reserve have a lower mortality, and lower events/hospitalisations. The presence of contractile reserve therefore offers a potential positive prognostic indicator when managing these patients.